Respiration measurement using fibre-optic deformation sensor. Issue 6 (26th March 2017) - Di, Haiting; Sun, Suping; Che, Ying
Abstract: Untreated fibre is not sensitive to bending deformation. In this paper, a fibre-optic deformation sensor has been developed by introducing a light leakage zone on one side of fibre, which measures bending deformation directly. A respiration measurement system based on fibre-optic deformation sensors is developed. Two fibre-optic sensors are bonded to an elastic belt that is fixed around the chest, which ensures the deformation curvature of the sensors changes during respiration. The light leakage zones of two sensors are arranged at the same cross-section of the belt and the directions of two light leakage zones are opposite. In this case, the throughput of one sensor increases and the other decreases during respiration. A differential system is established by these two fibre-optic sensors, which improves the sensitivity of the measurement system. The proposed fibre-optic respiration measurement system enables a quantitative assessment of the respiratory depth and respiratory rate.